Improving Concentration in Pencak Silat Athletes through Meditation Training - Fransiska, Nabila Yuniar; Natasha, Nayla; Vision, Najiha's; Susanti, Ruth Natalia; Mayangsari, Dewi (Yayasan Sinergi Kawula Muda, 2025)
Meditation is an effective technique for increasing focus and concentration, especially in the context of sports. This study aims to evaluate the effectiveness of meditation training in improving the concentration abilities of pencak silat athletes. Using an experimental approach, the training was carried out in three sessions divided into two meetings. Training success was measured using a pre-test and post-test design. The research results showed a significant increase in the athletes' ability to focus and concentrate after participating in the training. These findings support previous research results which state that meditation can increase concentration and self-control in athletes, so that they are able to execute strategies and techniques more effectively in competitions.